Performance of Procurement System in Ministries and Institutions through Integration of LKPP e-catalogue and LPSE Electronic Procurement System - Reginald, Reginald (Eduvest - Journal of Universal Studies, 2025)
Nowadays, every entrepreneur who runs a business must be able to master the latest technology in order to be able to run a digital business. If entrepreneurs are not able to keep up with technological developments, then the business they run will be left behind by their opponents. For entrepreneurs who run their business digitally and are oriented in the government sector, entrepreneurs must use the LKPP (Policy Institute for Procurement of Goods/Services) e-catalogue. This research focuses on the LKPP electronic catalog. The purpose of this research is to find out the process to the convenience felt while using the LKPP e-catalogue. This research uses supporting theories such as ERP (Enterprise Resource Planning), e-auction security, the bidding process, and also the tender process. This research method uses qualitative methods where the techniques used are observation, interviews, and documentation during the use of LKPP e-catalogue. The research was conducted starting from interviews with several selected sources and coding using NVIVO 14. The types of coding carried out are open coding, axial coding, and selective coding. The results of this study show that there are issues regarding the document preparation process, waiting time, system constraints, means for system improvement, and continuous development. The contribution of this research is the need for system improvements related to LKPP e-catalogue version 6.0.